Origins of regioselectivity of Diels-Alder reactions for the synthesis of bisanthraquinone antibiotic BE-43472B. - Hayden, A; Paton, R; Becker, J; Lim, Y; Nicolaou, K; Houk, K (2010)
The regioselectivities of several Diels-Alder reactions utilized en route to bisanthraquinone antibiotic BE-43472B are examined using density functional theory calculations. These reactions involve highly substituted dienes and juglone dienophiles, and there is an opposite regiochemical outcome for Diels-Alder reactions with beta-aryl substituted juglones when compared to reactions of unsubstituted juglone. In this article, the effect of an aromatic conjugating group bonded to juglone is explored.